XRD ANALYSIS FOR COPPER-GRAPHITE METAL MATRIX COMPOSITES (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In the present examination, endeavors have been made for the creation of Cu-graphite MMC by customary and sparkle plasma sintering (SPS) methods. The MMCs were described by x-beam diffraction (XRD). Diverse mechanical properties like thickness, mass hardness and wear study were likewise led. XRD spectra demonstrate the nearness of Cu, graphite and Cu2O crests which demonstrates that no communication amongst Cu and graphite happens amid creation. The nearness of a frail pinnacle of Cu2O demonstrates that slight oxidation of Cu happens amid sintering. It has been found that expansion of graphite into copper does not bring about much change in hardness because of the delicate way of graphite. Nonetheless, 90% and 97 % of hypothetical thickness have been acquired for routine sintered and SPS tests individually. Greatest Vickers hardness estimation of around 100 has been accomplished for Cu-1 vol. % graphite MMC when it is created by SPS. Be that as it may, a hardness estimation of 65 has been acquired for the same composite when it is created by ordinary sintering at 900Â°C for 60 minutes. The micrographs of Cu-graphite mirror the perfect interface and great similarity amongst lattice and support.Â